Adding Ginkgo biloba leaf extract to the diet as an antioxidant and studying its effect on carcass traits and immune performance of Ross 308 broilers - Ammar Taleb Diab Al-Tememy; Ali saleh Hassan Al-kinani (Zien Journals, 2022)
The experiment was carried out in the poultry field of the Department of Animal Production/College of Agriculture/ University of Diyala during the period from 4/9/2021 to 15/10/2021 to study the effect of adding ginkgo leaf extract to broiler diets as an antioxidant and study its effect on carcass traits and immune performance of birds The experiment was conducted using 225 unsexed 308 Ross broiler hybrid chicks at the age of one day, and the average weight of the chick was (43.62)g.
Keywords: chicks; average; carcass; weight